Institutional Structures in the Process of Developing Rural Areas - Borowiec, Janusz (Regional Barometer. Analyses & Prognoses, 2008)
The enterprise – understood as peoples’ aspiration to undertake activities, look for new solutions, utilize new opportunities and activities in order to find additional and alternative sources of income – constitutes an element of a the balanced economic development of rural areas. The process of the enterprise’s development means a higher diversity of income sources which subsequently provides for an opportunity to combine working on a farm with activities offered by the enterprise. The said process shows also an essential symbiosis between various entities active in the agro business sector i.e. privately owned farms, entities supplying and purchasing agricultural produce, banks and, also local government authorities. Entities running their business activity in a form of co-operative associations are essential links of a process of creating an institutional structure within rural areas. The said co-operative associations employ the activities of local communities and constitute grounds for transfer of means derived from various found-rising sources. Both the predispositions and experiences of co-operative associations lean towards an opinion that in fact co-operative associations thoroughly accomplish the assignment of local institutions to ensure a balanced economic development in rural areas.